The role of short-chain fatty acids in intestinal barrier function, inflammation, oxidative stress, and colonic carcinogenesis - Liu, Pinyi; Wang, Yanbing; Yang, Ge; Zhang, Qihe; Meng, Lingbin; Xin, Ying; Jiang, Xin (Pharmacological research, 2021)
[Display omitted] •Short-chain fatty acids are metabolites produced in the intestinal tract.•Two major SCFA signaling mechanisms are promotion of histone acetylation and activation of G-protein-coupled receptors.•SCFAs affect the regulation of inflammation, carcinogenesis, intestinal barrier function, and oxidative stress.•SCFAs have a high potential for a therapeutic use in human diseases Short-chain fatty acids (SCFAs), mainly including acetate, propionate, and butyrate, are metabolites produced during the bacterial fermentation of dietary fiber in the intestinal tract. They are believed to be essential factors affecting host health. Most in vitro and ex vivo studies have shown that SCFAs affect the regulation of inflammation, carcinogenesis, intestinal barrier function, and oxidative stress, but convincing evidence in humans is still lacking. Two major SCFA signaling mechanisms have been identified: promotion of histone acetylation and activation of G-protein-coupled receptors. In this review, we introduce the production and metabolic characteristics of SCFAs, summarize the potential effects of SCFAs on the four aspects mentioned above and the possible mechanisms. SCFAs have been reported to exert a wide spectrum of positive effects and have a high potential for therapeutic use in human-related diseases.